THE FINANCIAL PERFORMANCE ANALYSIS OF SUBANG REGENCY LOCAL GOVERMENT - Bisma Indrawan (Journal of Business Administration, 2023)
The aim of this research is to assess the Financial Performance of Subang District Local Government by analyzing the Budget Realization Reports (LRA). This study adopts a quantitative descriptive approach involving calculations based on financial data obtained to address the research objectives. The research is conducted at the Subang District Financial and Asset Management Agency (BKAD). Data collection relies on the documentation method. The data analysis technique used is quantitative descriptive, employing the following formulas: (1) Budget Growth, (2) Analysis of Revenue Budget Ratios: Degree of Decentralization, Local Financial Dependence, Local Financial Independence, Effectiveness and Efficiency of Local Own-source Revenue (PAD), Effectiveness and Efficiency of Local Taxes, (3) Analysis of Expenditure Alignment: Operating Expenditure to Total Expenditure, Capital Expenditure to Total Expenditure, Direct and Indirect Expenditure, (4) Expenditure Efficiency. The results indicate that the financial performance of Subang District Government during 2015-2017 can be considered excellent. This is evident through positive revenue growth, a high degree of decentralization with an average percentage of 100%, very low local financial dependence at 0%, and high local financial independence with a delegative relationship pattern of 100%. The average effectiveness of PAD is highly effective at 122.53%, while the average efficiency is very efficient at 4.01%. The average effectiveness of local taxes is highly effective at 115.48%, while the average efficiency is very efficient at 4.22%. The analysis of expenditure alignment shows that the average operating expenditure to total expenditure is 94.15%, and capital expenditure is 5.85%, indicating insufficient attention to regional development. The average direct expenditure is 74.24%, and indirect expenditure is 25.76%. The average expenditure efficiency is 81.89%. Based on this research, for future studies, it is recommended to include additional financial statements for analysis, such as the balance sheet and income statement. Furthermore, the Subang District Government is advised to maintain its current performance.